The Importance of Establishing a New Counterterrorism Unit at Local Level: Combining Different Perspectives in Policing - Eker, Ahmet; Ozkan, Ersan (European Scientific Journal, ESJ, 2016)
The number of terrorism related attacks and deaths of innocent people as a result of those terrorist assaults have been increasing. This was despite the huge amount of budget devoted towards fighting against terrorism by the governments. One of the reasons for being insufficient to reduce the number of terrorist attacks is the limited involvement of the local police agencies in the fight against terrorism. Most of them do not have separate terrorism units and are not full-time police officers. Those agencies which have separate units assign only four or less officers. As a result, their ability to get information on terrorism related activities and the level of information sharing with the federal and national agencies is very limited. It is suggested in this paper that each local police agency should establish a separate terrorism unit and assign sufficient number of full-time police officers. These officers and managers should be trained by national experts. Officers in these units should develop mutual trust with different groups that have diverse political and religious backgrounds. A strong relationship and cooperation should also be developed with other local and national agencies. In addition, each local police agency should prepare contingency plans prior to any attack.